Report of the Planning Committee on the 2018 Members’ Forum - McGill Community For Lifelong Learning (MCLL) (2018)
A Members’ Forum was held on 26 October 2018 to discuss the issue of peer learning at MCLL. The three major findings and the four recommendations are presented here

Selected Papers from the 2018 Conference on Community Education and Development: Perspectives on English-Speaking Blacks and Minorities - Black Community Resource Centre (BCRC) (2018)
The Black Community Resource Centre (BCRC) is a growing, resource-based organization that strengthens community capacity by providing professional support to organizations and individuals in need. The Centre is committed to helping visible minority youth rekindle their dreams, and achieve their full potential.We take a comprehensive approach to meet the needs of English-speaking youth. By referring to the “Holistic Project” approach through our community service, we recognize that youth have many needs (e.g., socio-cultural, educational, and economic, etc.) that must be addressed in order for youth to achieve their greatest potential in our society.
event-date: December 6, 2018/December 7, 2018
Keywords: Official Language Minority Community (OLMC)

NDG Community Strategic Action Plan 2016-2021 : List of Annexe : Part II - NDG Community Council (NDGCC) (2018)
This document is the first of three that collectively represent the NDG Community Strate- gic Plan 2016-2021. Part I is a report on the strategic planning and action planning pro- cess and presents the context, tools and outcomes of the NDG Community Strategic Plan. Part II includes annexes to this report with details, tools and other data. Part III presents the Action Plan 2018-2021.

NDG Community Strategic Action Plan 2016-2021 : Part I - NDG Community Council (NDGCC) (2018)
This document is the first of three that collectively represent the NDG Community Strate- gic Plan 2016-2021. Part I is a report on the strategic planning and action planning pro- cess and presents the context, tools and outcomes of the NDG Community Strategic Plan. Part II includes annexes to this report with details, tools and other data. Part III presents the Action Plan 2018-2021.

NDG Community Strategic Action Plan 2016-2021 : Part III - NDG Community Council (NDGCC) (2018)
This document is the first of three that collectively represent the NDG Community Strate- gic Plan 2016-2021. Part I is a report on the strategic planning and action planning pro- cess and presents the context, tools and outcomes of the NDG Community Strategic Plan. Part II includes annexes to this report with details, tools and other data. Part III presents the Action Plan 2018-2021.

Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)
Number of pages: 3

Turn into YES 12 : A Benefit Event and Silent Auction : Sponsorship Opportunity - Youth Employment Services (YES) (2018)

Food Security Resources - NDG Community Council (NDGCC) (2018)

Forum communautaire sur la santé de NDG : Améliorer les connaissances de la communauté sur l'accès aux services locaux de santé et de services sociaux : Rapport final - NDG Community Council (NDGCC) (2018)
Le Forum Communautaire sur la santé de NDG a eu lieu le samedi 21 octobre 2017, au Centre des Arts Crowley à Notre-Dame-de-Grâce. Son objectif était de fournir aux résidents de NDG, en particulier à ceux et celles vivant dans la précarité, l'occasion d'obtenir des informations sur les services de santé et services sociaux dans leur communauté afin de faciliter leur accès à ces ressources. Le forum a permis aux participants de rencontrer divers fournisseurs de services dans la communauté, de discuter des problèmes d'accès dans le contexte des réformes récentes au Québec et de participer à des ateliers thématiques sur des problèmes plus ciblés d'accès à la santé. Près de trente agences locales de santé, de services sociaux et de soutien, issues des secteurs public, privé et à but non lucratif avaient des kiosques au Forum, avec personnes-ressources présentes pour répondre aux questions des participants, présenter les services qu’elles fournissent et distribuer des brochures d'information aux personnes qui pensaient pouvoir bénéficier de leurs services. Le Forum a été conçu pour offrir aux résidents de la communauté de NDG des connaissances sur les services qui leur sont disponibles, et pour permettre aux organisations des secteurs public et communautaire de mieux comprendre les besoins de la communauté afin d’améliorer leurs services et les liens intersectoriels.

Ressources en sécurité alimentaire - NDG Community Council (NDGCC) (2018)

The NDG Community Health Forum : Improving Community Knowledge about Access to Local Health and Social Services: Final report - NDG Community Council (NDGCC) (2018)
The NDG Community Health Forum was held on Saturday, October 21, 2017 at the Crowley Arts Centre in Notre-Dame-de-Grâce. Its objective was to provide NDG residents, in particular those living in vulnerable situations, an opportunity to obtain information about health and social services in their community and how to access these services. The Forum enabled participants to meet with a variety of health and community service providers, discuss access issues in the context of recent reforms in Québec, and participate in themed workshops on more focused health challenges. Close to thirty local health agencies from the public, private and non-profit sectors had kiosks at the Forum, with resource people to introduce the services they provide and pamphlets participants could take home with them. The Forum was designed to empower community members with knowledge about available services, and provide public and community sector organizations with an opportunity to learn more about community needs in order to improve their services.

Semaji - Black Community Resource Centre (BCRC) (2018)
Number of pages: 10

Program Book for Winter/Spring 2018 - Youth Employment Services (YES) (2018)
issued: January, 2018/August, 2018

24th Jackie Robinson Golf Tournament - Black Academic Scholarship Fund (BASF) (2018)

Employee Resource Guide - NDG Community Council (NDGCC) (2018)

Guide de ressources d'emploi - NDG Community Council (NDGCC) (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)
Number of pages: 11

Semaji - Black Community Resource Centre (BCRC) (2018)
Number of pages: 7

Semaji - Black Community Resource Centre (BCRC) (2018)
Number of pages: 10

Digital Solutions to Connect Artistic Producers with Cultural Consumers - English Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2018)
Between January and March 2018, ELAN's Digital Solutions research project surveyed artists, arts organizations, publicists, journalists, media specialists and technical specialists, and hosted two focus group sessions.

Demographic Profile of the English-speaking Communities : Administrative Region of Montréal & the Rest of Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Improving Access to Health and Social Services and Information in the English Language - Prata, Ghislaine (2018)

Semaji - Black Community Resource Centre (BCRC) (2018)
Number of pages: 10

Report on the Proceedings of the Advancing Women in STEM Community Leaders Forum & Strategic Recommendations - Association for Canadian Studies (ACS) (Youth Employment Services (YES), 2018)
YES Montreal is currently leading one of 20 initiatives funded by Status of Women to advance gender equality in Canada. Advancing Women in STEM is a three-year grant project (2017-2020) that aims to address and identify solutions to a number of systemic challenges hindering women’s retention and access to leadership positions within the STEM industry. This initiative follows from two previous ones; in the inaugural project (2012-2015), YES conducted three annual gender-based analyses of Quebec’s technology sector and in the second project (2015-2017) developed a tailored mentorship model for women in Montreal’s STEM industry. The overarching goal of the Advancing Women in STEM project is to create systemic change within STEM companies by shifting institutional practices to promote inclusivity and leadership opportunities for women. Successfully achieving this goal is dependent on the collaboration and support of industry and community leaders, particularly the project’s advisory committee that consists of fifteen outstanding women leaders who are highly engaged in this initiative and its outcomes.

25th Jackie Robinson Golf Tournament : Sponsors - Black Academic Scholarship Fund (BASF) (2018)

Adaptation Initiative Project Guide 2014-2018 - Community Health and Social Services Network (CHSSN) (2018)
The CHSSN’s initiative to adapt health and social services is supported by an investment from Health Canada, through the Roadmap for Canada's Official Languages 2013–2018: Education, Immigration, Communities. This initiative is being undertaken in partnership with the Ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded in order to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English. The agreement also divided the roles and responsibilities among the CHSSN, the MSSS, and the health and social services agencies.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

L'initiative d'adaptation : guide des projets 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Job Posting : Events & Access Coordinator - State of the Arts III - English Language Arts Network (ELAN) (2018)

Job Posting : Project Manager - State of the Arts III - English Language Arts Network (ELAN) (2018)

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

The Newsletter : Fall 2018: Volume 29, No. 3 - McGill Community For Lifelong Learning (MCLL) (2018)
Number of pages: 12

Annual Report : 2017-2018 - NDG Community Council (NDGCC) (2018)

Rapport annuel : 2017-2018 - NDG Community Council (NDGCC) (2018)

Health and Social Service Resources for English-Speaking Communities in the East and North of Montreal : 2018 - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)
Number of pages: 7

Annual Report 2017-18 - The English Speaking Catholic Council (ESCC) (2018)

The Yellow Door : 2017-2018 Annual Report - Yellow Door (2018)